Aggregation-induced emission nanoparticles with NIR and photosensitizing characteristics for resistant bacteria elimination and real-time tracking. (2nd August 2021) - Yuan, Huanxiang; Li, Zelin; Bai, Haotian; Chen, Zhuo; Yao, Chuang; Jia, Shaochuan; Li, Li; Qi, Ruilian; Zhao, Cui-Hua
Abstract : Because of the steady increase in multi-drug-resistant bacterial infections, we developed a viable treatment strategy using new antibacterial nanomaterials with photosensitizing effects. Abstract : Because of the steady increase in multi-drug-resistant bacterial infections, we developed a viable treatment strategy using new antibacterial nanomaterials with photosensitizing effects. In this work, three triphenylamine derivates (TPA-2PE, TPA-PCN, and TPA-2PCN) and amphiphilic polystyrene maleic anhydride (PSMA) were used to successfully prepare three corresponding nanoparticles. Compared to TPA-2PE, the introduced cyano unit resulted in a redshift for TPA-PCN and TPA-2PCN with near-infrared (NIR) emission. The specific aggregation-induced emission (AIE) characteristic contributed to the retentive photophysical property and the increased fluorescence quantum yield (QY) of these luminous molecules in nanoparticles. Our in vitro study indicated that the nanoparticles were able to tightly bind to the surface of bacteria by hydrogen bond interaction, and their bacterial toxicity was successfully directed against antibiotic-resistant Escherichia coli . The bactericidal performance was further amplified under white light irradiation by the supplied photosensitizing effect. Additionally, the killed bacteria were stained with the nanoparticles and subsequently emitted NIR emission, regardless of the interference of bacterial autofluorescence. The sterilization effects of the nanoparticles were tracked in situ and qualitatively characterized by the NIR self-reporting function. In the protocol reported herein, we describe all the essential factors for addressing antibiotic resistance, and therefore, this work includes all the necessary criteria for designing additional antibacterial nanomaterials in the future.